2014
DOI: 10.1007/s10909-013-1063-7
|View full text |Cite
|
Sign up to set email alerts
|

Development of MMC Gamma Detectors for Nuclear Analysis

Abstract: Non-destructive assay (NDA) of nuclear materials would benefit from gamma detectors with improved energy resolution in cases where line overlap in current Ge detectors limits NDA accuracy. We are developing metallic magnetic calorimeter (MMC) gamma-detectors for this purpose by electroplating 150 µm thick Au absorbers into microfabricated molds on top of Au:Er sensors. Initial tests under non-optimized conditions show an energy resolution of 200 eV FWHM at 60 keV. Monte Carlo simulations illustrate that this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Figure 4.9 shows a 300 µm thick test pattern on a glass slide. This demonstrated that the process could achieve an aspect ratio that was sufficient to keep neighboring pixels on the hard X-ray chip separated [82].…”
Section: New Absorber Processmentioning
confidence: 95%
“…Figure 4.9 shows a 300 µm thick test pattern on a glass slide. This demonstrated that the process could achieve an aspect ratio that was sufficient to keep neighboring pixels on the hard X-ray chip separated [82].…”
Section: New Absorber Processmentioning
confidence: 95%
“…This motivates our development of γ -detectors based on metallic magnetic calorimeters [8]. Here, we illustrate the use of MMC γ -detectors in a nuclear safeguards application with a direct measurement of Pu-242 γ -rays, and show that our MMCs have sufficient energy resolution for NDA of Pu samples that contain Pu-242.…”
Section: Introductionmentioning
confidence: 90%
“…Cryogenic γ -detectors can overcome some of the limitations of HPGe detectors in nuclear safeguards due to their higher energy resolution and higher peak-tobackground ratio [3][4][5][6][7][8]. This motivates our development of γ -detectors based on metallic magnetic calorimeters [8].…”
Section: Introductionmentioning
confidence: 99%